Advice given by community members to pregnant women: a mixed methods study. Issue 1 (December 2016) - Verma, Bianca; Nichols, Lauren; Plegue, Melissa; Moniz, Michelle; Rai, Manisha; Chang, Tammy
Abstract Background Smoking and excess weight gain during pregnancy have been shown to have serious health consequences for both mothers and their infants. Advice from friends and family on these topics influences pregnant women's behaviors. The purpose of our study was to compare the advice that community members give pregnant women about smoking versus the advice they give about pregnancy weight gain. Methods A survey was sent via text messaging to adults in a diverse, low-income primary care clinic in 2015. Respondents were asked what advice (if any) they have given pregnant women about smoking or gestational weight gain and their comfort-level discussing the topics. Descriptive statistics were used to characterize the sample population and to determine response rates. Open-ended responses were analyzed qualitatively using grounded theory analysis with an overall convergent parallel mixed methods design. Results Respondents (n  = 370) were 77 % female, 40 % black, and 25 % reported education of high school or less. More respondents had spoken to pregnant women about smoking (40 %, n  = 147) than weight gain (20 %, n  = 73). Among individuals who had not discussed either topic (n  = 181), more reported discomfort in talking about weight gain (65 %) compared to smoking (34 %;p  < 0.0001). Advice about smoking during pregnancy (n  = 148) was frequently negative, recommending abstinence and identifying smoking as harmful for baby and/or mother. Advice about weight gain in pregnancy (n  = 74) revealed a breadth of messages, from reassurance about all weight gain ("Eat away" or "It's ok if you are gaining weight"), to specific warnings against excess weight gain ("Too much was dangerous for her and the baby."). Conclusions Many community members give advice to pregnant women. Their advice reveals varied perspectives on the effects of pregnancy weight gain. Compared to a nearly ubiquitous understanding of the harms of smoking during pregnancy, community members demonstrated less awareness of and willingness to discuss the harms of excessive weight gain. Beyond educating pregnant women, community-level interventions may also be important to ensure that the information pregnant women receive supports healthy behaviors and promotes the long-term health of both moms and babies.